Respostas
respondido por:
15
2a-b=-8
3a+2b=9
Vou resolver pelo método Adição, e para isso vou multiplicar a primeira equação por 2
4a-2b=-16
3a+2b=9
________
7a+0=-7
7a=-7
a=-7/7
a=-1
3a+2b=9
3.(-1)+2b=9
-3+2b=9
2b=9+3
2b=12
b=12/2
b=6
3a+2b=9
Vou resolver pelo método Adição, e para isso vou multiplicar a primeira equação por 2
4a-2b=-16
3a+2b=9
________
7a+0=-7
7a=-7
a=-7/7
a=-1
3a+2b=9
3.(-1)+2b=9
-3+2b=9
2b=9+3
2b=12
b=12/2
b=6
Perguntas similares
7 anos atrás
7 anos atrás
7 anos atrás
9 anos atrás
9 anos atrás